Transformation of the Visual Afterimage Under Subject's Eye and Body Movements and the Visual Field Constancy Mechanisms. (August 2015) - Zenkin, Gary M.; Petrov, Alexander P.
Two types of positive afterimages differing in their structural complexity—called poor and rich —were used to investigate the visual field constancy mechanisms during eye and head movements. In the case of a poor afterimage, consistent with Emmert's law, every eye and head movement caused the afterimage to appear moving (in exactly the same way), unlike a real object, which appeared to remain stationary during those same eye and head movements (although its retinal image moved opposite to the eye movement). However, in the case of a rich afterimage, the afterimage appeared stationary during eye movements, while a small stationary test light in the real space appeared to move, violating Emmert's law. It is suggested that, in these two cases, the different apparent transformations reflected functioning of different constancy mechanisms. Both mechanisms implement projection of retinal images upon a hypothetical constant visual screen in strict accordance with the subject's movements but in two different ways. The experiments have indicated that, during binocular fusion, the visual afferent system is able to use information from the structural organization of the visual flow to implement the visual field stability and to calculate gaze direction independently of proprioceptive signals.